2022
DOI: 10.1111/cbdd.14029
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of potential inhibitors for autophagy‐related protein 8 as antileishmanial agents

Abstract: Leishmaniasis is a tropical neglected disease, which is caused by an intramacrophagic parasite, Leishmania. It is endemic to 89 different countries (Piscopo & Mallia Azzopardi, 2007). It occurs in 0•7-1 million people every year (Burza et al., 2018). The genus Leishmania consists of 29 species, and each may be responsible for causing species and host response-specific diseases (Torres-Guerrero et al., 2017). The majority of Leishmania species responsible for causing leishmaniasis are Leishmania major, Leishman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The role of ATG8 in L. donovani for its survival mechanism and infectivity showed it as a drug target. Molecular docking and molecular dynamic simulation studies show the enticing role of thiabendazole derivatives that impede the survival mechanisms by affecting ATG8 (Guhe et al, 2022), while virtual screening of natural ligand library had been performed against ATG8 of L. donovani, showing that urolithin-A which is formed by combinations of coumarin and isocoumarin stably blocked ATG8 (Rahman et al, 2022).…”
Section: Exploration Of the Potential Modulator To Modulate Autophagy...mentioning
confidence: 99%
See 2 more Smart Citations
“…The role of ATG8 in L. donovani for its survival mechanism and infectivity showed it as a drug target. Molecular docking and molecular dynamic simulation studies show the enticing role of thiabendazole derivatives that impede the survival mechanisms by affecting ATG8 (Guhe et al, 2022), while virtual screening of natural ligand library had been performed against ATG8 of L. donovani, showing that urolithin-A which is formed by combinations of coumarin and isocoumarin stably blocked ATG8 (Rahman et al, 2022).…”
Section: Exploration Of the Potential Modulator To Modulate Autophagy...mentioning
confidence: 99%
“…Targeted protein/pathway Respective potential drug References 1 Hsp90 17-AAG (17-N-allylamino-17demethoxygeldanamycin) (Petersen et al, 2012), (Santos et al, 2014) 2 LABCG2, transporter protein of the ABC subfamily Transporter's mutations or peptide designing against proteins (Manzano et al, 2017), (Kabra et al, 2020) 3 Autophagic process which is crucial for dysfunction in L. donovani promastigotes CLP (cryptolepine) (Guhe et al, 2022), (Rahman et al, 2022) Frontiers in Molecular Biosciences frontiersin.org platform for the analysis, interpretation, and visualization of Leishmania omics data (transcriptomics, proteomics, and metabolomics) in the context of metabolic pathways and offers a systematic approach to structuring the increasing information regarding Leishmania biochemical networks (Doyle et al, 2009).…”
Section: Snmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study explored inhibitors against ATG8 and found increased ROS activity and reduced L. donovani presence in THP1 macrophage cells. 111 Similarly, different anti-leishmanial compounds targeting apoptosis via increased ROS have been also identified recently. 112−114 Thus, ATG8-mediated parasite autophagy and apoptosis have become interesting drug targets to test against leishmaniasis.…”
Section: Interplay Of Autophagy and Phagocytosis By Macrophagesmentioning
confidence: 99%
“…A normal functional autophagy and the subsequent phospholipid homeostasis in the parasites are essential for the parasites’ normal differentiation from promastigotes to amastigotes and the infectivity in the host by hijacking host autophagy and reducing the host’s defense mechanism. A recent study explored inhibitors against ATG8 and found increased ROS activity and reduced L. donovani presence in THP1 macrophage cells . Similarly, different anti-leishmanial compounds targeting apoptosis via increased ROS have been also identified recently. Thus, ATG8-mediated parasite autophagy and apoptosis have become interesting drug targets to test against leishmaniasis.…”
Section: Autophagic Machinery Regulation In Response To Leishmaniamentioning
confidence: 99%